Clinical outcomes after the introduction of direct antiviral agents for patients infected with genotype 1b hepatitis C virus depending on the regimens: A multicenter study in Korea. Issue 6 (11th February 2019) - Kwon, Jung Hyun; Yoo, Sun Hong; Nam, Soon Woo; Kim, Hee Yeon; Kim, Chang Wook; You, Chan Ran; Choi, Sang Wook; Cho, Se Hyun; Han, Joon‐Yeol; Song, Do Seon; Chang, U Im; Yang, Jin Mo; et al.
Abstract: Background: A real‐life study is essential outside clinical trials. The aim is to evaluate the clinical outcomes of direct acting agents (DAA) for patients with chronic hepatitis C (CHC) in real practice. Methods: We analyzed 590 consecutively enrolled patients with CHC‐1b who received DAAs since 2015, when DAAs were introduced in Korea. The patients were checked for resistance‐associated variants (RAV) against nonstructural protein 5A inhibitors and then daclatasvir/asunaprevir or sofosbuvir based regimens were chosen. Results: The frequency of patients with cirrhosis and prior hepatocellular carcinoma (HCC) was 29.2% and 4.7%, respectively. For the RAV test, 10% were positive and in 3.6% the result was "indeterminate." Overall, 518 patients were treated with a 24‐week regimen of daclatasvir/asunaprevir, 72 patients (RAV positive 75%) were treated with 12 weeks regimen of ledipasvir/sofosbuvir or daclatasvir/sofosbuvir. The SVR12 was 94.0% in the daclatasvir/asunaprevir, 98.2% in the ledipasvir/sofosbuvir, and 100% in the daclatasvir/sofosbuvir group. A total of 93.3% of SVR12 in the RAV‐"indeterminate" patients was not difference 95.0% in the RAV‐negative patients. Up to 1 year, de novo HCC occurrence and recurrence developed in 2.6% and 17.8%, respectively. HCC was more frequent in cirrhotic patients than in noncirrhotic patients ( P  = 0.000). α Fetoprotein (AFP) level at the end of treatment was a predicting factor for de novo HCC. Conclusions: Optimizing the choice of DAAs according to RAV test resulted in high SVR among CHC‐1b Korean patients. This real practice multicenter cohort study suggests the importance of AFP and HCC surveillance in cirrhotic patients even after successful HCV therapy.